"Intermediate" and "Advanced" Accounting: The Role of "Economic Consequences". - Zeff, Stephen A. (The Accounting Review, 1980)
In this article the author comments on the impact of economic consequences on intermediate and advanced accounting. The author uses some textbooks to discuss these accounting practices. In all of the textbooks, an accounting model has dealt with the matching of costs with revenues in order to arrive at a proper measure of income. The emergence of the decision usefulness approach to accounting theory has led textbook authors to refer more to the possible uses of accounting information. The article also aims to argue for a course of reform.